Endogenous TFP, business cycle persistence and the productivity slowdown in the euro area - Michaela Schmöller; Martin Spitzer (European Central Bank (ECB), 2020)
This paper analyses the endogeneity of euro area total factor productivity and its role in business cycle amplification by estimating a medium-scale DSGE model with endogenous productivity mechanism on euro area data. In this framework, total factor productivity evolves endogenously as a consequence of costly investment in R&D and adoption of new technologies. We find that the endogeneity of TFP induces a high degree of persistence in the euro area business cycle via a feedback mechanism between overall economic conditions and investment in productivity-enhancing technologies. As to the sources of the euro area productivity slowdown, we conclude that a decrease in the efficiency of R&D investment is among the key factors generating the pre-crisis productivity slowdown, while starting from the Great Recession a shock to liquidity demand is identified as the most important driving force. The endogenous technology mechanism further exerts a dampening effect on the in ation response following a recessionary shock and hence has important implications for both the negligible fall in in ation during the Great Recession, as well as the sluggish increase of in ation in the subsequent recovery.
Keywords: E24; E32; O31; 330; Endogenous Productivity; Euro Area Business Cycles; Weak Growth; Low Inflation